Operationalization of Mindfulness in Organization - Konte, Aboubacar Garba (Journal of Finance, Business and Management Studies, 2023)
Nowadays many companies are looking for management innovation as they are continuously trying to enhance the quality of their employees in order to improve the organization’s ability to adapt to changes and competitive pressures. How to build an organization based on cooperation and solidarity and enhance the collective wisdom of members has become the focus of research. In the innovative exploration of some companies, the concept of leader mindfulness has been introduced into many companies (Google, Apple, Sony, ING, etc.). The related research in the field of management is still in its infancy. Because leader mindfulness is very valuable to organizations, this article aims to study the psychological construct of this concept, so as to encourage leaders to adopt active and effective ways to lead organizations. This work adopts a qualitative approach of research. On this basis a pilot study based on MBSR was conducted. The managers experienced an 8-week MBSR training and practice. We conducted in-depth interviews with them to analyze the internal structure of mindfulness and its impact on the trainees from the perspective of management practice. The results show that mindfulness training has a positive impact on managers’ improvement of core abilities, including interpersonal skills and the ability to determine priorities, which are very important for improving management efficiency.